Factors associated with the higher prevalence of common mental disorders: integrative review - Oliveira, W. L.; Cavalcanti, P. P. (Scientific Electronic Archives, 2018)
The term Common Mental Disorders (CMD) was created by Goldberg and Huxley to encompass a population with depressive and anxious symptoms, such as insomnia, fatigue, irritability, forgetfulness, difficulty of concentration, and somatic complaints which do not fit the formal criteria for diagnosing anxiety and depression according to the psychiatric classification. The global and national prevalence of mental disorders in the primary care represents one-third of the demand. Taking into account the occurrence of CMD in the population and the demand for attention in the health services, the aim of this work was to identify factors associated with higher prevalence of CMD in the adult population in Brazil according to scientific evidence, as well as to describe possibilities of strategies to prevent it. An integrative review was carried out using the following databases: Scientific Electronic Library Online (SciELO) and Virtual Health Library (BVS). The search was directed through the descriptors: Common Mental Disorders; prevalence; Self Reporting Questionare-20, having as guiding question: What factors are associated with the higher prevalence of CMD in Brazil? The following exclusion criteria were used: articles with research and/or publication prior to 2007, not presented by the search strategies chosen and those that did not focus on the adult population. The studies were compared and categorized by content similarity for analysis; four categories were established which were associated with a higher prevalence of CMD: gender, income, work-related aspects and other factors (physical activity, schooling and age). The integration of the nineteen selected articles points as factors associated with a higher prevalence of CMD: work-related aspects, being female and having a low income. Other factors such as physical activity, schooling and age were also listed. CMDs are considered a public health problem involving several mechanisms. In view of the results presented, is possible to observe that both the primary care systems, as well as the organizations have the possibility of designing prevention and treatment strategies to mitigate the illness of the adult population.